Classic congenital adrenal hyperplasia with unilateral functional adrenal cortical adenoma: case report - Qin Yan; Huancheng Su; Xuan Jing; Sufen Li; Xujiao Ji; Zhiping Zhang; Yanni Wang; Xia Huang; Tingting Xue; Xueqing Wu; Xiangrong Cui (Taylor & Francis Group, 2024)
Congenital adrenal hyperplasia (CAH) is a group of autosomal recessive disorders related to adrenal steroid biosynthesis, and mainly caused by mutations in the CYP21A2 gene encoding 21-hydroxylase. Adrenal tumors are common in CAH, but functional adrenal tumors are rare. Here, we report a 17-year-old female with virilized external genitalia and primary amenorrhea, accompanied by a right adrenal tumor. Her 17-OHP level was normal, cortisol and androgen levels were significantly elevated, and the tumor pathology showed adrenal cortical adenoma. Gene testing for CYP21A2 showed c.518T > A in exon 4 and c.29313C > G in intron 2. The possibility of untreated classic CAH with 21-OH deficiency causing functional adrenal cortical adenoma should be considered. When clinical diagnosis highly considers CAH and cannot rule out the influence of functional adrenal tumors' secretion function on 17-OHP, gene mutation analysis should be performed.